Development and initial validation of the Psychological Characteristics of Developing Excellence Questionnaire - Macnamara, A.; Collins, D. (Journal of Sports Sciences, 2011)
The development of talent is a complex process mediated by a host of psychological, social, physical, and environmental variables. Unfortunately, the multiple processes involved in talent development are frequently ignored by the systems and protocols employed in sport. Modern approaches to talent development are beginning to stress the initial possession, then subsequent development, of generic psychological characteristics (e.g. psychological characteristics of developing excellence; MacNamara, Button, & Collins, 2010a50. MacNamara , Á. , Button , A. and Collins , D. 2010a . The role of psychological characteristics in facilitating the pathway to elite performance. Part 1: Identifying mental skills and behaviours . The Sport Psychologist , 24 : 52 - 73 .